Strategies for Sustainable Corn Farming Development in Bima Regency - Muhammad Ridwan; Lina Karlinasari; Hariyadi (Jurnal Penelitian Pendidikan IPA, 2025)
Bima Regency is one of the main centers of corn production in Indonesia, playing a significant role in food security and the local economy. However, the sustainability of corn farming in this region faces various challenges, particularly environmental degradation, carrying capacity issues, price fluctuations, and dependence on chemical inputs. This study aims to analyze corn production conditions over the past ten years, assess the sustainability of corn farming, and develop strategies for sustainable corn farming in Bima Regency. The methods used in this study include production data analysis for the 2015-2024 period, sustainability analysis using the Multidimensional Scaling (MDS) approach with Rapfish software, and strategy formulation using the SWOT method. The sustainability index for corn farming in Bima Regency was found to be 55,88, indicating a moderately sustainable level, with ecological and institutional dimensions posing the main challenges. The study highlights the science-based approach to sustainability, linking environmental science with the development of adaptive farming strategies. Based on the SWOT analysis, key strategies for corn development include climate risk mitigation through green infrastructure and adaptive cultivation, reducing dependence on chemical fertilizers with local organic fertilizers, and strengthening farmer group institutions and marketing. The implementation of these strategies is expected to enhance farmers' economic resilience, improve environmental conditions, and contribute to the long-term sustainability of corn farming in Bima Regency.